Optimal capital, regulatory requirements and bank performance in times of crisis: Evidence from France - de Bandt, Olivier; Camara, Boubacar; Maitre, Alexis; Pessarossi, Pierre (Journal of Financial Stability, 2018)
The recent implementation of the Basel III framework has re-ignited the debate around the link between actual capital levels, performance and capital requirements in the banking sector. There is a dominant view in the earlier empirical literature in favor of a positive effect of capital on performance. Using panel data gathered by the French supervisor, we also find evidence of this beneficial effect of capital, but try to go one step further by distinguishing between regulatory and voluntary capital. Using a two-step estimation procedure, and controlling for many factors (risk, asset composition, etc.), we show that voluntary capital, i.e. capital held by banks irrespective of their regulatory requirements, turns out to be the sole component of capital that affects performance positively. In contrast, the effect of regulatory capital on profitability appears to be insignificant, indicating that so far the increase in capital requirements has not been detrimental to bank profitability in France.